First report of field-evolved resistance to insecticides in Spodoptera frugiperda (Lepidoptera: Noctuidae) from Punjab, Pakistan. - Hafiz Azhar Ali Khan; Ansar Ali (PLoS ONE)
The fall armyworm, Spodoptera frugiperda, is one of the major destructive pests of agriculture in Pakistan. The widespread use of insecticides for the management of S. frugiperda has resulted in the field-evolved resistance to insecticides in different strains worldwide. However, field-evolved resistance to insecticides has not yet been reported in S. frugiperda from Pakistan. Following reports of control failure of S. frugiperda in Punjab, Pakistan, a study was planned to investigate resistance to insecticides from different classes in field strains of S. frugiperda to confirm whether the resistance was indeed evolving. Here, we explored resistance to spinetoram, emamectin benzoate, indoxacarb, diflubenzuron, methoxyfenozide, chlorpyrifos and cypermethrin in seven field strains and compared them with a laboratory susceptible reference (Lab-SF) strain of S. frugiperda. Compared with the Lab-SF strain at the LC50 levels, the field strains exhibited 24.8-142.7 (spinetoram), 33.4-91.4 (emamectin benzoate), 30.1-90.6 (indoxacarb), 16.1-38.4 (diflubenzuron), 18.4-51.8 (methoxyfenozide), 37.1-222.9 (chlorpyrifos), and 61.9-540.6 (cypermethrin) fold resistance ratios (RRs). In the presence of detoxification enzyme inhibitors [piperonyl butoxide (PBO) and S,S,S-tributyl phosphorotrithioate (DEF)], the toxicity of all the insecticides, with the exception of spinetoram, was significantly enhanced in the tested field strains of S. frugiperda, providing insight into the metabolic mechanism of resistance. Additionally, compared with the Lab-SF strain, the resistant field strains exhibited elevated activities of detoxification enzymes such as glutathione S-transferases (GST), carboxylesterases (CarE) and mixed-function oxidases (MFO). Overall, the findings of the present study provide robust evidence of field-evolved resistance to insecticides in S. frugiperda, which needs to be managed to minimize yield losses of different crops caused by this global pest.